The educational pathway to Advanced Practice for the physiotherapist: A systematic mixed studies review - Kaitlyn Maddigan; Chris Davis; Brendan Saville; Kathryn Nishimura; Jennifer Van Bussel; Andrews K. Tawiah; Katie L. Kowalski; Alison B. Rushton (PLoS ONE, 2025)
Background Advanced Practice Physiotherapy (APP) is a higher level of practice grounded in 4 pillars: clinical practice, leadership, education and research. A critical step toward successful integration and sustainability of APP in healthcare systems is understanding the educational pathway to APP. Objectives 1) To describe the post-licensure educational pathways that physiotherapists engage in to advance their level of practice. 2) To evaluate demonstration of the pillars of APP by the physiotherapist after traversing a post-licensure educational pathway. Methods This systematic mixed studies review is reported in accordance with PRISMA and pre-registered (PROSPERO: CRD42024499563). 8 databases plus the grey literature were searched. 2 independent reviewers determined eligibility, extracted data, assessed quality (QuADS) and determined the overall confidence in the cumulative evidence (GRADE-CERQual). Results 81 studies (18 qualitative, 17 mixed methods, 46 quantitative) were included in a data based convergent qualitative synthesis. 6 distinct post-licensure educational pathways were described and evaluated: Masters level education, residency and fellowship programs, accredited area of practice education, mentorship, multiple encounter courses and single encounter courses. Conclusion There is a high level of confidence (GRADE-CERQual) in the finding that Masters level education consistently resulted in all 4 pillars demonstrated by the physiotherapist. Masters level education appears to be the optimal pathway to APP.